Little-studied French-language literary criticism of I.A. Bunin’ works in the light of the first wave of Russian émigrés - Svetlana Garziano (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2019)
Contemporary studies on French criticism of I.A. Bunin’s works were conducted in three main areas: literary criticism, published by French authors, different reviews of Bunin’s books and articles, timed to the receipt of the Nobel Prize. The article analyzes previously unexplored or obscure texts written in French by representatives of the first wave of émigrés. The work explores four topics: interwar French-language émigré criticism of I.A. Bunin’s works, N.K. Kulman’s article “Ivan Bunin. His literary activity in France” (“Ivan Bunin. Son activité littéraire en France”, 1928), the image of I.A. Bunin in V.S. Posner’s book “Panorama of modern Russian literature” (“Panorama de la littérature russe contemporaine”, 1929) and in the light of literary reflections expressed during the meetings of the Franco-Russian studio (Paris, October 1929 — April 1931). A review of émigré criticism in French makes it possible to highlight some of the main features of Bunin’s poetics, such as the writer's leading place in émigré literature as the heir to realism and the main branch of great Russian literature, excessive corporeality and materiality of Bunin’s world, and the fundamental theme of love and death, which makes it possible to understand the ontological meaning of life. The mention of this writer plays a pivotal role in the French-language criticism of Russian émigrés, manifested in literary articles, reviews, books, reference articles and personal letters.